Regulation of transcription by DNA supercoiling in Mycoplasma genitalium: global control in the smallest known self-replicating genome. - DORMAN, CHARLES (My University, 2011)
The mollicute Mycoplasma genitalium causes sexually transmitted disease in humans. It has recently come to widespread public attention through its involvement in pioneering synthetic biology experiments. The 580-kilo-base-pair genome of M. genitalium contains just 470 genes, few of which seem to encode conventional transcription regulators. This raises the important question of how does this simple organism control its gene expression? The finding that the transcription of an osmotically inducible gene encoding a lipoprotein is sensitive to antibiotics that inhibit the activity of DNA gyrase, the enzyme that introduces negative supercoiling into DNA, raises the possibility that changes in DNA supercoiling provide a regulatory mechanism for controlling transcription in M. genitalium.
PUBLISHED
Published online 02 June 2011
Keywords: Genetics; Infection; Mycoplasma genitalium; Genes & Society; Immunology, Inflammation & Infection